Ghost ship [videorecording (DVD)] - Beck, Steve; Silver, Joel; Zemeckis, Robert, 1952-; Adler, Gilbert; Hanlon, Mark; Pogue, John; Margulies, Julianna, 1966-; Eldard, Ron, 1964-; Harrington, Desmond, 1976-; Washington, Isaiah; Dimitriades, Alex, 1973-; Urban, Karl, 1972-; et al. (Warner Bros. Entertainment : Distributed by Warner Home Video, 2007)
Salvagers discover the Antonia Graza, an Italian luxury liner with a dark secret. The passenger ship has been missing since 1962, floating adrift on the Bering Sea, the salvagers claim the vessel as their own. But the Antonia Graza in not uninhabited. Once towing of the ghost ship towards harbor has begun, a series of bizarre ocurrences happen and the group becomes trapped inside the ship, which they soon learn is inhabited by a demonic creature.